2016
DOI: 10.1017/s2040174416000325
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes and anthropometric measures of Indigenous Australian women and their infants in the Gomeroi gaaynggal cohort

Abstract: Indigenous Australians continue to experience disparities in chronic diseases, many of which have nutrition-related trajectories. Optimal nutrition throughout the lifespan is protective for a number of adverse health outcomes, however little is known about current dietary intakes and related anthropometric outcomes of Indigenous women and their infants. Research is required to identify nutrition issues to target for health promotion activities. The Gomeroi gaaynggal programme is an ongoing, prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…Patterns of consumption are generally consistent with those from localised quantitative and qualitative studies (23)(24)(25) and with national NATSINPAS data, noting differences in outcome definition and age group: 26 (22) . Consumption of fruit drink and flavoured milk was also common among children in the present sample, as has been observed in previous studies (19,21,22,24,25) . Children's consumption of fruit drink (24,25,43) and flavoured milk may be encouraged by caregivers who perceive this to be a healthy choice, despite the potentially high sugar content.…”
Section: Overviewsupporting
confidence: 73%
See 1 more Smart Citation
“…Patterns of consumption are generally consistent with those from localised quantitative and qualitative studies (23)(24)(25) and with national NATSINPAS data, noting differences in outcome definition and age group: 26 (22) . Consumption of fruit drink and flavoured milk was also common among children in the present sample, as has been observed in previous studies (19,21,22,24,25) . Children's consumption of fruit drink (24,25,43) and flavoured milk may be encouraged by caregivers who perceive this to be a healthy choice, despite the potentially high sugar content.…”
Section: Overviewsupporting
confidence: 73%
“…There is a high prevalence of SSB consumption in Australia, and particularly high consumption prevalence and volume among Aboriginal and Torres Strait Islander peoples (18)(19)(20) . While the measurement approaches and populations have varied across studies, there is consistent localised and national quantitative evidence of high SSB intake by Aboriginal and Torres Strait Islander children in the first 3 years of life (Table 1) (18,(21)(22)(23)(24)(25)(26) . For example, data from the National Aboriginal and Torres Strait Islander Nutrition and Physical Activity Survey (NATSINPAS) indicated that 26•0 (95 % CI 13 •5, 38•5) % of Aboriginal and Torres Strait Islander children aged 2-3 years had consumed cordial on the day prior to interview, compared with 10•3 (95 % CI 6•4, 14•2) % of non-Indigenous children in the Australian Health Survey (18,21,22) .…”
mentioning
confidence: 99%
“…Furthermore, poor food patterns and diet quality during pregnancy can exacerbate adverse maternal health outcomes by contributing to excessive gestational weight gain (49) and post-partum weight retention (50) . Although Ashman et al (51) have previously investigated the dietary intakes of Indigenous Australian women and their infants, the present study evaluates the dietary pattern of Indigenous Australian women during pregnancy from the Gomeroi gaaynggal cohort, relative to national recommendations. Although Ashman et al (51) have previously investigated the dietary intakes of Indigenous Australian women and their infants, the present study evaluates the dietary pattern of Indigenous Australian women during pregnancy from the Gomeroi gaaynggal cohort, relative to national recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the aspects of maternal diet and nutrient intakes during pregnancy that differ from national recommendations may assist with development of targeted nutrition interventions and inform public health policies seeking to optimise maternal nutrition. Although Ashman et al (51) have previously investigated the dietary intakes of Indigenous Australian women and their infants, the present study evaluates the dietary pattern of Indigenous Australian women during pregnancy from the Gomeroi gaaynggal cohort, relative to national recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Common over-the-counter medications such as vitamin and mineral supplements may also significantly affect serum lipids and inflammatory markers [ 31 , 32 , 33 ]. Post-partum dietary data for this cohort has been published elsewhere [ 34 ], but it is beyond the scope of this analysis to include the effects of dietary intakes and patterns here.…”
Section: Discussionmentioning
confidence: 99%